Volume loss during muscle reinnervation surgery is correlated with reduced CMAP amplitude but not reduced force output in a rat hindlimb model - Lowe, Alexis L.; Rivera Santana, Maria V.; Bopp, Taylor; Quinn, Kiara N.; Johnson, Johnnie; Ward, Christopher; Chung, Tae Hwan; Tuffaha, Sami; Thakor, Nitish V. (Frontiers in Physiology, 2024)
Introduction: Muscle reinnervation (MR) surgery offers rehabilitative benefits to amputees by taking severely damaged nerves and providing them with new denervated muscle targets (DMTs). However, the influence of physical changes to muscle tissue during MR surgery on long-term functional outcomes remains understudied. Methods: Our rat hindlimb model of MR surgery utilizes vascularized, directly neurotized DMTs made from the lateral gastrocnemius (LG), which we employed to assess the impact of muscle tissue size on reinnervation outcomes, specifically pairing the DMT with the transected peroneal nerve. We conducted MR surgery with both DMTs at full volume and DMTs with partial volume loss of 500 mg at the time of surgery (n = 6 per group) and measured functional outcomes after 100 days of reinnervation. Compound motor action potentials (CMAPs) and isometric tetanic force production was recorded from reinnervated DMTs and compared to contralateral naïve LG muscles as positive controls. Results: Reinnervated DMTs consistently exhibited lower mass than positive controls, while DMTs with partial volume loss showed no significant mass reduction compared to full volume DMTs (p = 0.872). CMAP amplitudes were lower on average in reinnervated DMTs, but a broad linear correlation also exists between muscle mass and maximum CMAP amplitude irrespective of surgical group (R2 = 0.495). Surprisingly, neither MR group, with or without volume loss, demonstrated decreased force compared to positive controls. The average force output of reinnervated DMTs, as a fraction of the contralateral LG’s force output, approached 100% for both MR groups, a notable deviation from the 9.6% (±6.3%) force output observed in our negative control group at 7 days post-surgery. Tissue histology analysis revealed few significant differences except for a marked decrease in average muscle fiber area of reinnervated DMTs with volume loss compared to positive controls (p = 0.001). Discussion: The results from our rat model of MR suggests that tissue electrophysiology (CMAPs) and kinesiology (force production) may recover on different time scales, with volumetric muscle loss at the time of MR surgery not significantly reducing functional outcome measurements for the DMTs after 100 days of reinnervation.